Association between Early Antibiotic Administration and In-Hospital Mortality in Moderate and Severe COVID-19 Patients - Lie Khie Chen; Jason Nathanael; Sharifah Shakinah; Adeline Pasaribu; Robert Sinto; Leonard Nainggolan; Adityo Susilo (Jurnal Penyakit Dalam Indonesia)
Introduction. Patients with moderate and severe COVID-19 generally receive antibiotic therapy with consideration of the possibility of co-infection or secondary bacterial infection which clinically is difficult to distinguish from COVID-19 symptoms. Overuse of antibiotics can lead to an increased risk of bacterial resistance to antibiotics which is associated with poor outcomes in COVID-19 patients. This study aimed to assess the effect of early antibiotic administration on mortality in moderate and severe COVID-19 patients. Methods. An observational study with a retrospective cohort design was conducted at Dr. Cipto Mangunkusumo Hospital. Data were obtained from medical records of patients admitted from March to September 2020. Patients who received early antibiotics were defined as patients who received antibiotics hospital, 108 subjects were included in this study, 74 (68.5%) with moderate degrees and 34 (31.5%) with severe degrees. Early antibiotics were administered to 79 (73.1%) subjects with a median start time of one day. The results of the bivariate analysis did not find a significant effect of early antibiotic administration on mortality in moderate or severe COVID-19 patients (p=0.42). Subgroup analysis based on the degree of disease also found no significant results. Conclusion. There is no relationship between early antibiotic administration and mortality of moderate and severe COVID-19 patients.